Makna Ruang Sosial Pada Hunian Masyarakat di Kampung Batik Jetis Sidoarjo - Kusumastuti, Rahmalia; Suryasari , Noviani (Jurnal Mahasiswa Departemen Arsitektur, 2026)
Kampung Batik Jetis in Sidoarjo is a residential area that has developed alongside home-based batik tulis production activities. Social, economic, and cultural dynamics influence how domestic spaces are used, organized, and interpreted by the community. This study aims to examine the meaning of social space within residential dwellings in Kampung Batik Jetis using Henri Lefebvre’s the production of space theoretical framework. The research employs a qualitative approach with deductive reasoning and an exploratory constructivist paradigm. Five batik tulis home-based enterprises, Batik Tulis Namiroh, Amri Jaya, Amali, Kamsatun, and HI were selected through purposive sampling. Data were collected through field observations and semi-structured interviews, and subsequently analyzed based on the three dimensions of the production of space: spatial practice, representations of space, and representational space. The findings indicate that residential space is a dialectical product of production activities, owners’ planning intentions, and symbolic values. Most dwellings are categorized as museum space, characterized by the dominance of conceptual space, while others function as generic space, with a stronger emphasis on perceptual space to maintain a balance between domestic privacy and the sustainability of batik production activities. Keywords: Batik Village, The Production of Space, Social Space